2016
DOI: 10.1016/j.ejmech.2015.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel cyclic lipopeptides from a positional scanning combinatorial library with enhanced antibacterial and antibiofilm activities

Abstract: Treating bacterial infections can be difficult due to innate or acquired resistance mechanisms, and the formation of biofilms. Cyclic lipopeptides derived from fusaricidin/LI-F natural products represent particularly attractive candidates for the development of new antibacterial and antibiofilm agents, with the potential to meet the challenge of bacterial resistance to antibiotics. A positional-scanning combinatorial approach was used to identify the amino acid residues responsible for driving antibacterial ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 62 publications
0
28
1
1
Order By: Relevance
“…The sample was combined with an additional 4 mL of neutralizing solution and homogenized. Serial dilutions were made from all culture samples and the extent of microbiological contamination assessed using the Spiral Plater System (Spiral Biotech, Norwood, MA) as previously described . Pseudomonas Agar‐base supplemented with Cetrimide Sodium Nalidixate (Remel Inc, Lenexa, KS) was used to isolate P. aeruginosa from the wound biofilms.…”
Section: Methodsmentioning
confidence: 99%
“…The sample was combined with an additional 4 mL of neutralizing solution and homogenized. Serial dilutions were made from all culture samples and the extent of microbiological contamination assessed using the Spiral Plater System (Spiral Biotech, Norwood, MA) as previously described . Pseudomonas Agar‐base supplemented with Cetrimide Sodium Nalidixate (Remel Inc, Lenexa, KS) was used to isolate P. aeruginosa from the wound biofilms.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, Bionda et al . [15] used a positional-scanning combinatorial method to screen a cyclic lipopeptide library (peptides derived from fusaricidin/LI-F) against multidrug resistant pathogens. The lead peptide from this study showed activity against all ESKAPE pathogens at 110 μM.…”
Section: Antimicrobial Peptides With Potential To Fight Biofilm-relatmentioning
confidence: 99%
“…When wounds become colonized with biofilm-forming bacteria, the ability to heal is compromised and they can become very difficult to treat 13. Leg ulcers, a common chronic wound often found in immunocompromised patients,14 are predominantly colonized by P. aeruginosa (88%) and Staphylococcus aureus (33%),3 two of the most prevalent species found in chronic wound biofilms 15,16. Furthermore, resistance to the antibiotics routinely used to treat biofilms only augments the crisis.…”
Section: Introductionmentioning
confidence: 99%